Clinical application of Kirschner wires combined with 5-Ethibond fixation for patella fractures - Liang, Yuan; Hu, Jinlong; Zhang, Pei; Zhang, Jiale; Yang, Lixun; Zhang, Wendong; Chen, Jiaxin; He, Jinshan; Fang, Yongchao; Zhou, Yuelai; Chen, Pengtao; Wang, Jingcheng (Frontiers in Surgery, 2023)
Background: Patella fractures that require surgeries are conventionally treated using Kirshner wires (K-wires) and stainless steel wires (SSWs). In recent years, the non-absorbable polyester has been reported to have excellent outcomes clinically. Therefore, the goal of our study was to evaluate the effects of Kirschner wires combined with 5-Ethibond on treating patellar fractures. Methods: From July 2018 to January 2022, twenty-two patella fracture patients were treated with Kirschner wires combined with 5-Ethibond. Radiographs of knees were used to evaluate fracture healing and hardware complications. The clinical results were evaluated through the functional score, knee joint ROM, and Bostman patella fracture functional score. Results: The patients’ average age of patients was 57.4 ± 11.9 (range 33–74) years. The mean follow-up time was 15.2 ± 7.6 (range 4–36) months. The mean operation time was 56.8 ± 8.7 (range 45–80) minutes. The entire sufferers had bony union at an average of 10.5 ± 1.9 (range 8–14) weeks. At the final follow-up, the mean range of postoperative ROM was 123.4 ± 14.6° (range 95–140), and the functional score was 28.7 ± 1.2 (range 26-30) points. No patient exhibited internal fixation failure, and no symptomatic implants and skin complications were recorded. Conclusions: The fixation approach using K-wires combined with 5-Ethibond has a lower complication rate and delivers superior clinical results. This research reveals that such technology is a safe and prospective substitution for conventional metal fixation approaches.